﻿New species and records of the genus Hybos Meigen (Diptera, Empidoidea, Hybotinae) from Wuyishan National Park, China - Meilin Li; Ding Yang (ZooKeys, 2023)
Wuyishan National Park is well known for its rich biodiversity. Previously, only five species of Hybos Meigen, 1803 were known to occur in this region. In this study, 27 species of the genus Hybos from Wuyishan National Park are reviewed based on comparative morphological characteristics. Among these, nine species are described as new to science: Hybos brevidigitatus sp. nov., Hybos constractus sp. nov., Hybos curvitibia sp. nov., Hybos dazhulanus sp. nov., Hybos fujianensis sp. nov., Hybos leucopogus sp. nov., Hybos longidigitatus sp. nov., Hybos modificatus sp. nov., and Hybos wuyishanus sp. nov. Diagnoses, detailed descriptions, remarks, colored illustrations, distributions, and some of the female terminalia characteristics are provided for nine new species. In addition, 13 species of this genus are reported for the first time in Wuyishan National Park. A key to Hybos species from Wuyishan National Park is also given.